CONSTITUTIONAL PRINCIPLES INTRODUCED BY THE TAX REFORM: AHUMANIZED APPROACH (REMUNOM, 2026)
The Brazilian tax reform introduced by Constitutional Amendment No. 132 of 2023 represents oneof the most significant recent transformations in the national tax system, particularly regarding thereorganization of consumption taxation and the incorporation of new constitutional principlesguiding fiscal activity. In this context, the present study aims to analyze the constitutional principlesintroduced by the Brazilian tax reform, considering a humanized approach to taxation and itsinstitutional, economic, and social impacts. To achieve this objective, a qualitative research designwas adopted, based on a bibliographic review of recent scientific articles addressing tax reform,constitutional tax principles, and the restructuring of the fiscal system. The results indicate that thereform seeks to simplify the tax structure, reduce distortions arising from tax cascading, andstrengthen principles such as simplicity, transparency, and tax neutrality. It is also observed that thereorganization of consumption taxation may contribute to greater legal certainty, administrativeefficiency, and improvements in the economic environment. It is concluded that the Brazilian taxreform represents a process of institutional reconfiguration of the fiscal system, in which theincorporation of new constitutional principles points toward the development of a more rational,transparent, and socially oriented tax model.